Psycho-physiological responses of mountain bike riders during anaerobic and aerobic testing - Paludo, A. C.; Cook, C. J.; Owen, J. A.; Woodman, T.; Owen, S.; Crewther, B. T. (Journal of Science and Cycling, 2017)
The objective was to compare the descriptive characteristics and psycho-physiological responses of elite and non-elite mountain bike riders to anaerobic and aerobic cycle testing. Nineteen male mountain bike riders were assessed for descriptive characteristics (anthropometric, VO2max) and for psychological (state-anxiety and perceived exertion) physiological (heart rate variability (HRV), testosterone (T) and cortisol (C) salivary hormones), and performance responses to a single bout of anaerobic and aerobic cycle test. The athletes were separated into elite (n=6) and the non-elite sub-divided into non-elite I (n=6), those with more experienced at riding, and non-elite II (n=7) who had less. No group difference were found for descriptive characteristics as well as for the state-anxiety, T and C hormones changes (P>0.05). A significantly higher performance in both tests and a higher perceived exertion during the aerobic test were reported by the elite group compared to non-elite II group (P<0.05). Also, the elite group produced a significantly larger HRV response than non-elite I and II (P<0.001) in rest period. In conclusion, we can speculate that, the cumulative effect of mountain bike training could influence in the psychophysiological variables such as the great cardiac autonomic responses and perceived of exertion in male riders towards a better cycling performance.